Dietary exposure to acrylamide among the Malaysian adult population - Nur Hidayah, Jamaludin; Abdul Razis, Ahmad Faizal; Jambari, Nuzul Noorahya; Chai, Lay Ching; You, Lijun; Sanny, Maimunah (Elsevier, 2024)
This study aimed to estimate the Malaysian adult population's current dietary exposure and margin of exposure (MOE) to the carcinogenic processing contaminant, acrylamide. A total of 448 samples from 11 types of processed foods were collected randomly throughout Malaysia in the year 2015 and 2016. Acrylamide was analysed in samples using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) with a limit of detection (LOD) of 10 μg/kg and a limit of quantification (LOQ) of 25 μg/kg. The highest average level of acrylamide (772 ± 752 μg/kg) was found in potato crisps, followed by French fries (415 ± 914 μg/kg) and biscuits (245 ± 195 μg/kg). The total acrylamide exposure for the adult Malaysian was 0.229 and 1.77 μg/kg body weight per day for average and high consumers, respectively. The MOE were 741 and 1875 for the average consumer based on cancer and non-cancer effects of acrylamide, respectively. Meanwhile, for high consumers, the MOE is 96 for cancer and 243 for non-cancer effects. These findings indicate potential carcinogenic risks from acrylamide exposure among Malaysian adults, especially in Malay and other Bumiputra groups compared to Chinese, Indian, and other ethnic groups, while non-cancer effects appeared less concerning.